The Gateway to Computer Science Excellence
+2 votes

The value of the Boolean expression (with usual definitions) $(A’BC’)’ +(AB’C)’$ is

  1. $0$
  2. $1$
  3. $A$
  4. $BC$
in Digital Logic by Boss (17.5k points)
recategorized by | 116 views

3 Answers

+1 vote

$(A'BC')'+(AB'C)'\\=\left\{(A')'+B'+(C')'\right\}+\left\{A'+(B')'+C'\right\};~[\text{Applying De Morgan's law}]\\=A+B'+C+A'+B+C';~[\because (X')'=X]\\=(A+A')+(B+B')+(C+C');~[\text{Commutative and Associtive laws}]\\=1+1+1;~[\because X+X'=1 \text{ as the Complement law}]\\=1;~[\because 1+1=1 \text{ in Boolean algebra}]$


So the correct answer is B.

by Active (3.5k points)
edited by
0 votes

Option B) 1

Given $(A’BC’)’ +(AB’C)’$

$(A+B'+C) + (A'+B+C')$


by Boss (16.3k points)
0 votes
Answer : B

(A′BC′)′+(AB′C)′  =>     (A+B'+C) + (A'+B+C')

(A+A')+(B+B')+(C+C') = 1
by Junior (959 points)
Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
50,741 questions
57,251 answers
104,680 users